PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP CITRA PERUSAHAAN PADA PT. TOBA PULP LESTARI PORSEA - Bela Novita; Kristanty M. N. Nadapdap (Jurnal Ilmu Manajemen METHONOMIX, 2018)
The purpose of this research is to examine the effect of Corporate Social Responsibility on corporate image. The case study took place in PT. Toba Pulp Lestari. The research population was 30 families or about 90 people in the Desa Siruar, Parmaksian Porsea District; and used purposive sampling as the sampling technique, resulted in 70 people as respondents. Data analysis in this research is Simple Linear regression. The result shows that Corporate Social Responsibility has a positive and significant effect on corporate image. Conclusion, limitations and suggestions for future research are explained.